2020
DOI: 10.1155/2020/3986348
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene Attenuates Cocultured BV-2 Microglial Inflammation-Mediated SH-SY5Y Neuronal Oxidative Injury via SIRT-1 Signalling

Abstract: Microglial inflammation plays an important part in the progression of multiple neurological diseases, including neurodegenerative diseases, stroke, depression, and traumatic encephalopathy. Here, we aimed to explore the role of pterostilbene (PTE) in the microglial inflammatory response and subsequent damage of cocultured neural cells and partially explain the underlying mechanisms. In the coculture system of lipopolysaccharide-activated BV-2 microglia and SH-SY5Y neuroblastoma, PTE (only given to BV-2) exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…BV-2, a microglial cell line, (purchased from Cell Bank of Chinese Academy of Sciences, Beijing, China), was used to further illustrate the role of the p38MAPK/ATF2 pathway in isoflurane induced neuroinflammation. The cells were cultured and maintained in Dulbecco’s modified Eagle’s medium (DMEM), which contained 10% fetal bovine serum, 10 μg/mL penicillin, and 10 U/mL streptomycin, as previously reported ( Wang et al, 2018 ; Zhu et al, 2020 ). The cells were cultivated under the conditions of 95% air and 5% CO 2 at 37°C and passaged by trypsinization for further study ( Wang et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…BV-2, a microglial cell line, (purchased from Cell Bank of Chinese Academy of Sciences, Beijing, China), was used to further illustrate the role of the p38MAPK/ATF2 pathway in isoflurane induced neuroinflammation. The cells were cultured and maintained in Dulbecco’s modified Eagle’s medium (DMEM), which contained 10% fetal bovine serum, 10 μg/mL penicillin, and 10 U/mL streptomycin, as previously reported ( Wang et al, 2018 ; Zhu et al, 2020 ). The cells were cultivated under the conditions of 95% air and 5% CO 2 at 37°C and passaged by trypsinization for further study ( Wang et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was determined by the CCK-8 method (Cell Counting kit-8, Tongren Institute of Chemistry, Japan) ( Zhu et al, 2020 ). The cells were incubated with DMEM and CCK-8 medium for 3 h, and the absorbance value was measured using a marker at a wavelength of 450 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CNS, SIRT-1 plays an important role in promoting neurodevelopment, delaying brain senescence, maintaining homeostasis, and modulating circadian rhythm ( Herskovits and Guarente, 2014 ; Xu J. et al, 2018 ). Furthermore, a growing number of studies have shown that SIRT-1 exhibits a key role in regulating neuroinflammation via inhibiting NACHT domain-, leucine-rich repeat-, and PYD-containing protein 3 (NLRP3) inflammasome activation, toll-like receptor (TLR) 4 signaling, nuclear factor- (NF-) κB pathway, and IL-1β transcription, which may relate to the modulating of microglial function ( Zhang et al, 2019 ; Zhu et al, 2020 ). In the in vivo study, elevated levels of inflammatory cytokines, decreased expression of SIRT1 and microglial infiltration were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Pterostilbene (PTE; trans-3,5-dimethoxy-4′-hydroxystilbene; Figure 1 A), a natural stilbenoid occurring in grapes and berries, is a dimethylated analog of resveratrol [ 3 ]. PTE exhibits several remarkable pharmacological activities [ 4 ] including antiaging, anticancer, anti-diabetes, and neuroprotection. In addition, Park et al [ 5 ] demonstrated that PTE inhibited the PDGF-BB-induced cell growth of vascular smooth muscle cells in rats through inhibition of the Akt-dependent pathway.…”
Section: Introductionmentioning
confidence: 99%